Weak tectonics: the ambiguous role of materiality in the work of contemporary Japanese architects SANAA - Yang, Jing (2018)
As the overlap of real and virtual spaces takes place more and more frequently in our daily lives, it could be said that our sensibility towards embodied physical space is being affected by our experience of the virtual world. This raises the question of how architecture should respond to these changes. It seems there is a confrontation between the necessarily material dimension of architecture and the increasingly immaterial nature of the information age. A new strand of Japanese architects is pushing the limits of the dematerialisation of architecture, which has been called, by some critics, “weak architecture”. Some of the distinctive features of this weak architecture are simplicity, transparency and formal austerity, as well as a peculiar ambiguity in the expression of materiality.